Why Not All the Powerful Abuse? The Competitive Effects of Psychological Distance and Self-Control - Huang, Caiyun; Tian, Siyu (Frontiers in Psychology, 2021)
Building on the social distance theory of power, this study proposes the positive and negative mechanisms of power – and their impact – on abusive supervision from the competitive perspectives of psychological distance and self-control. The boundary effects of independent self-construal are also analyzed. The study’s hypotheses are tested through a questionnaire and an experimental study. The Study 1 data were collected from 422 supervisors and subordinates from five private enterprises and one state-owned enterprise in Eastern China. Study 2 was conducted through a scenario-based experiment in which 180 part-time MBA students from a university in Eastern China participated. All data were tested using polynomial regression analysis and a bootstrapping appraisal. The results revealed that: (1) the relationship between power and abusive supervision is not significant. (2) Psychological distance mediates the relationship between power and abusive supervision. High power leads to higher psychological distance, which in turn strengthens abusive supervision. (3) Self-control mediates the relationship between power and abusive supervision. High power leads to higher self-control, which in turn weakens abusive supervision. (4) The mediating effect of psychological distance is stronger, and the mediating effect of self-control is weaker when independent self-construal is high, rather than low. At the end of the paper, the theoretical and practical implications are discussed.